What are exosomes and how can they be used in multiple sclerosis therapy?. (April 2014) - Pusic, Aya D; Pusic, Kae M; Kraig, Richard P
<x xml:space="preserve">Abstract</x> Current treatment options for multiple sclerosis are limited and consist of immunosuppressors or agents to prevent immune infiltration of the brain. These therapies have potentially harmful side effects and do little to promote myelin repair. Instead, we suggest using exosomes, naturally occurring small vesicles that exert influence through the delivery of mRNA, microRNA and protein. Dendritic cells can be cultured from bone marrow and stimulated to release exosomes. When administered to the brain, these exosomes significantly increase myelination and improve remyelination following injury by prompting preoligodendrocytes to differentiate into myelin producing cells. Additionally, they are non-toxic and can easily cross the blood-brain barrier and, thus, have great potential as a therapeutic.